Ship Bow Force-Deformation Curves for Ship-Impact Demand of Bridges considering Effect of Pile-Cap Depth - Wei Fan; Wancheng Yuan (Shock and Vibration)
Since static analysis procedures in the vessel impact-resistant design codes neglect dynamic amplification effects related to bridge mass, ship-impact responses of bridges may be potentially underestimated. For this reason, several dynamic vessel-impact analysis techniques had been recently proposed, where a force-deformation curve was employed to model the vessel bow stiffness. Most of the recent works mainly focused on the force-deformation curves of the barge bows rather than the ship bows. In this paper, a high-resolution finite element model is developed to obtain the ship bow force-deformation curves. The global and local characteristics of the ship bow force-deformation curves are discussed based on the finite element crush analyses between the ship bows and the rigid walls. Effect of pile-cap depth on the force-deformation curves (rather than only impact forces) is studied in detail, and the corresponding empirical equations are developed using an energy ratio method. Finally, a practical example of ship-bridge collision is investigated to validate the force-deformation curves considering the effect of pile-cap depth. It is found from the case study that the effect of pile-cap depth plays an important role in quantifying structural demand under impact loads. The case study also indicates that the developed equations are reasonable in practical applications.